Blood loss in one-stage bilateral total knee arthroplasty: cruciate-retaining vs. posterior stabilized. A propensity score-matched analysis - Laoruengthana Artit; Tantimethanon Thanawat; Santisathaporn Nopparat; Inta-ngam Thisayapong; Pongpirul Krit; Rattanaprichavej Piti (SICOT-J)
Introduction: Although single-stage bilateral total knee arthroplasty (BTKA) presents several advantages, higher perioperative blood loss is a potentiate drawback that is still inevitable. Cruciate retaining (CR) TKA may theoretically result in less blood loss, offer better proprioception, and more physiologic kinematics compared to posterior stabilized (PS) TKA. The objective of this study was to compare perioperative blood loss and recovery among patients who underwent CR and PS BTKA. Methods: A cohort of 46 CR BTKA and 80 PS BTKA performed by a single surgeon were retrospectively evaluated. Identical surgical techniques and perioperative care were provided to all patients. Propensity score matching was utilized to compare blood loss, a visual analog scale (VAS) for postoperative pain level, morphine consumption, knee flexion arc, and length of stay (LOS). Results: Comparing CR BTKA and PS BTKA, drain output was 206.44 mL vs. 194.89 mL (p = 0.47), calculated blood loss was 886.23 mL vs. 724.89 mL (p = 0.05), and blood transfusion rate was 18% vs. 17% (p = 1.00). Additionally, CR BTKA had higher VAS than PS BTKA, at 6 h: 5.74 vs. 3.78 (p < 0.001), and at 12 h: 5.80 vs. 4.74 (p = 0.02). CR BTKA group had higher morphine consumption (26.87 mg vs. 19.74 mg; p = 0.01) in the first 48 h. CR BTKA showed significantly less knee flexion angle during 48–72 h postoperative. Conclusions: The use of the CR prosthesis in BTKA could not demonstrate a superiority over the PS design in terms of blood loss, and recovery of knee function during the acute postoperative period.